(untitled) (Research, Society and Development, 2021)
The pandemic of the new Coronavirus (COVID-19) has brought about a series of changes around the world. Education had to readjust to serve all students at all levels of education. However, problems were evidenced on several aspects, mainly due to the low accessibility of the students. Thus, understanding the students’ view of Emergency Remote Education (ERE) is of paramount importance for the better readjustment of classes, considering that millions of students in Brazil do not have basic infrastructure like computer and internet, to continue classes through ERE. In this sense, this research aimed to identify the possibilities and challenges in the learning of high school students at ERE. In the methodological process of this investigation with a qualitative approach, a questionnaire applied via Google Forms was used, with the students of a state school. The results indicate as possibilities, the continuity of studies, being able to study at home and flexible hours; the absence of physical contact and dialogue with teachers, caused learning difficulties as a consequence.